Bridging cultures: the role of school’s cultural diversity climate and cultural sensitivity in immigrant parents’ school involvement - Mera-Lemp, María José; Pizarro, José J.; Guglielmetti-Serrano, Florencia (Frontiers in Psychology, 2025)
Parents’ involvement in children’s education has been identified as a significant predictor of students’ school achievement and psychological outcomes. In the case of immigrant parents, research has suggested that low educational levels, poor incomes, and pertaining to minority cultural groups negatively affect their participation in both school and home academic activities. Nevertheless, little is known about the influence of schools’ approaches to cultural diversity and parents’ intercultural competencies on their commitment to children’s schooling processes. This study aims to examine the relationships between cultural diversity climate at school, cultural sensitivity, and school involvement among 751 Venezuelan and Peruvian immigrant parents settled in Chile and (2) to determine the possible influence of cultural sensitivity on the relationship between cultural diversity climate and parents’ school involvement. Results show that sociodemographic variables had limited effects on their school involvement, while cultural diversity climate, and cultural sensitivity had a greater influence. Implications for understanding immigrant parents’ relationships with schools and designing intervention programs are discussed.